MAKNA HIDUP SEBAGAI FAKTOR DALAM MENGHADAPI KESEPIAN PADA LANSIA DI PANTI JOMPO PANTI SOSIAL LANJUT USIA HARAPAN KITA INDRALAYA - Dwi Hurriyati; Velza Indita Putri (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Loneliness among older adults living in residential social care institutions is influenced not only by reduced social interaction but also by how individuals interpret and assign meaning to their life experiences after encountering various changes associated with aging. This condition suggests that meaning in life may serve as an important psychological resource associated with the experience of loneliness, although empirical evidence within the context of Indonesian residential care facilities remains limited. Accordingly, this study examined the relationship between meaning in life and loneliness among older adults residing at Harapan Kita Elderly Social Care Center, Indralaya. A quantitative approach with a correlational design was employed involving 20 participants selected through purposive sampling. Data were collected using valid and reliable questionnaires and analyzed with the Statistical Package for the Social Sciences (SPSS) through descriptive statistics, assumption testing, and correlation analysis. The findings revealed a correlation coefficient of r = −0.462 with a significance value of p = 0.040 (p < 0.05), indicating a significant negative relationship between meaning in life and loneliness. Older adults with higher levels of meaning in life tended to report lower levels of loneliness. These findings highlight the importance of developing psychosocial interventions that integrate social engagement, spiritual activities, and the enhancement of meaning in life to promote psychological well-being among older adults living in residential social care institutions. ABSTRAK Kesepian pada lansia yang menetap di panti sosial tidak hanya berkaitan dengan berkurangnya interaksi sosial, tetapi juga dipengaruhi oleh cara individu memaknai perjalanan hidupnya setelah menghadapi berbagai perubahan pada masa lanjut usia. Kondisi tersebut menunjukkan bahwa meaning in life berpotensi menjadi sumber daya psikologis yang berkaitan dengan pengalaman loneliness, meskipun bukti empiris pada konteks panti sosial di Indonesia masih terbatas. Penelitian ini diarahkan untuk menganalisis hubungan antara makna hidup dan kesepian pada lansia yang tinggal di Panti Sosial Lanjut Usia Harapan Kita Indralaya. Pendekatan kuantitatif dengan desain korelasional diterapkan pada 20 responden yang dipilih melalui teknik purposive sampling. Data diperoleh menggunakan kuesioner yang telah memenuhi persyaratan validitas dan reliabilitas, kemudian dianalisis dengan Statistical Package for the Social Sciences (SPSS) melalui statistik deskriptif, pengujian prasyarat analisis, dan uji korelasi. Analisis menghasilkan koefisien korelasi sebesar -0,462 dengan nilai signifikansi 0,040 (p < 0,05), yang memperlihatkan adanya hubungan negatif yang signifikan antara makna hidup dan kesepian. Temuan ini mengindikasikan bahwa lansia yang memiliki tingkat kebermaknaan hidup lebih tinggi cenderung mengalami kesepian yang lebih rendah. Bukti tersebut memperkuat pentingnya pengembangan program psikososial yang mengintegrasikan aktivitas sosial, spiritual, dan penguatan makna hidup sebagai upaya mendukung kesejahteraan psikologis lansia di lingkungan panti sosial.